2020
DOI: 10.1080/02670836.2020.1783618
|View full text |Cite
|
Sign up to set email alerts
|

Thermal desorption spectroscopy evaluation of hydrogen-induced damage and deformation-induced defects

Abstract: Thermal desorption spectroscopy (TDS) was performed on ultra-low carbon (ULC) steel with various degrees of hydrogen-induced damage and deformation-induced defects. First, the extent to which hydrogen-induced damage manifests itself in TDS measurements was evaluated. Application of multiple test conditions on cold deformed ULC steel with and without the presence of hydrogen-induced damage showed that such damage did not appear as a hydrogen signal on the TDS spectra. Second, interesting features observed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The main desorption peak of L-PBF 316L SS presents a relatively low value of activation energy for hydrogen desorption, 28 ± 4 kJ/mol, implying the presence of a reversible trap. According to previously published works [28][29][30]39,[42][43][44][45], this trap can be ascribed to an elastic stress field around dislocation or second-phase particles (E a ~0-20 kJ/mol), or a dislocation core (E a ~20-35 kJ/mol). An additional peak is observed at higher temperatures and its activation energy was found to be 62 ± 5 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main desorption peak of L-PBF 316L SS presents a relatively low value of activation energy for hydrogen desorption, 28 ± 4 kJ/mol, implying the presence of a reversible trap. According to previously published works [28][29][30]39,[42][43][44][45], this trap can be ascribed to an elastic stress field around dislocation or second-phase particles (E a ~0-20 kJ/mol), or a dislocation core (E a ~20-35 kJ/mol). An additional peak is observed at higher temperatures and its activation energy was found to be 62 ± 5 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for a better understanding of the behavior of the material in a hydrogen environment, it is important to study the characteristics of hydrogen traps. While there are numerous studies regarding hydrogen trapping in conventionally produced ASS [28][29][30][31][32], to the best of our knowledge, there is a lack of information on this issue about L-PBF ASS.…”
Section: Introductionmentioning
confidence: 99%
“…However, still some hydrogen desorbed even after annealing at higher temperatures and therefore the peak was linked to the combined action of vacancies and dislocations. Laureys et al [ 93 ] also identified vacancies as an active trapping site in a cold‐rolled ultralow‐carbon steel. However, in their case the trapping by vacancies resulted in a small distinct second peak at the high‐temperature side of the main peak, resulting from trapping by dislocations and grain boundaries.…”
Section: The Interaction Of Microstructural Defects With Hydrogen Revealed By Ifmentioning
confidence: 99%
“…Several studies on the trapping of hydrogen by vacancies in steel have been performed using TDS. [27,[91][92][93][94][95][96][97][98][99] Nagumo et al [91] observed a single desorption peak after tritium charging of a tensile-strained low-carbon (0.025 wt% C) steel and attributed it to trapping of tritium by vacancies. This was based on the introduction of the peak by cold work and rapid decrease of the peak upon annealing at low temperatures; i.e., annealing at 473 K did already result in a significant reduction of the amount of tritium desorbed.…”
Section: The Role Of Vacanciesmentioning
confidence: 99%
See 1 more Smart Citation